ANALISIS PELAPORAN KEUANGAN PONDOK PESANTREN TAHFIDZUL QUR’AN WAHDAH ISLAMIYAH KOLAKA BERDASARKAN PEDOMAN AKUNTANSI PESANTREN - Sari, Muspita; Turi, La Ode; Syahrir, Sasmita Nabila (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze whether the financial reporting of Pondok Pesantren Tahfidzul Qur’an Wahda Islamiyah Kolaka is in accordance with ISAK 335. The research employs a qualitative approach with a descriptive method. Data were collected through observation, direct interviews with the Head of Pondok Pesantren Tahfidzul Qur’an Wahda Islamiyah Kolaka, and documentation.The findings indicate that the financial reporting of Pondok Pesantren Tahfidzul Qur’an Wahda Islamiyah Kolaka, based on the Pesantren Accounting Guidelines, has not been fully implemented properly and does not yet comply with ISAK 335. This is mainly due to the lack of knowledge and human resources in preparing the pesantren’s financial statements, resulting in very simple records that only include income and expenditure, leaving several indicators unfulfille The researcher recommends that Pondok Pesantren Tahfidzul Qur’an Wahda Islamiyah Kolaka study accounting systems more thoroughly, particularly financial reporting, in order to improve the accuracy and organization of its financial records. Keywords: Financial Reporting, Islamic Boarding School, Islamic Boarding School Accounting Guidelines